Attitudes of Greek-Canadians toward Mental Illness: Pathways and Barriers to Mental Health Care - Athenaios, Penelope (Études helléniques / Hellenic Studies, 1999)
This study examined the relationship between cultural attitudes towards mental illness and patterns of utilization of mental health care services and community resources among Greek-Canadian families in Montreal. Data wascollected from three different sources, a) Literature review; b) (qualitative) personal interviews of eighteen family caregivers; and c) (qualitative) interviews of six community key informants. Verbatim transcripts wereanalyzed to explore the effect of cultural and traditional family values on attitudes relevant to seeking psychiatric services. The qualitative analysis of the data lends support to the contention that the stigmatization of mental illness in the Greek culture as well as the adherence of Greek-Canadians, to traditional values appears to be among the determining factors contributing to underutilization of mental health care services. Through analysis of the responses there were identified major concerns such as the language barrier, and primary needs such as: a) cultural-sensitive approach by the practitioners; b) introduction of new courses and the modification of the old ones pertaining to mental illness and cultural minorities by the professional schools; c) the need to recruit professionals from the community; d) the need for education and outreach programs within the community; d) the need for education and outreach programs within the community; e) the need for the community to have theira own chronic health care facility, etc.